Використання CFD для розрахунку спіральної камери та колон статора високонапірної радіально-осьової гідротурбіни - Миронов, Костянтин Анатолійович; Олексенко, Юлія Юріївна; Бондаренко, Дар’я Юріївна (НТУ "ХПІ", 2018)
На основі результатів CFD аналізується гідравлічний розрахунок підводу радіально-осьової гідротурбіни: спіральної камери, статорного кільця та колон статора. Розрахунок спроектованої спіральної камери високонапірної радіально-осьової гідротурбіни здійснюється на підставі припущення про симетричний потік потенційної осі. З метою зменшення гідравлічних втрат було обрано кут охоплення спіралі 360 ˚, згідно до рекомендацій для високонапірних турбін. Було обране статорне кільце розтрубного типу для кращого розподілу води. Спроектовані спіральна камера, статорне кільце і колони статора аналізуються та перевіряються за допомогою CFD при різних витратах води та масових витратах, як індивідуально так і з усією проточною частиною турбіни. Припущення щодо збереження моменту імпульсу або потенційного потоку перевіряється за допомогою CFD.

Spiral casing of a hydraulic turbine is a very important part for the uniform distribution of the kinetic energy of water along the periphery of the guide vanes and runner. It guides the water at optimum angle from the spiral casing and the stay ring through the guide vanes into the runner to provide an appropriate response between the entire water flow and the runner. The stay ring of the spiral casing is responsible for its mechanical strength and provides water through the stay vanes. The article analyzes the hydraulic calculation of a spiral casing, a stay ring and stay vanes. Verification of hydraulic calculation is carried out by developing a spiral casing of a high-pressure Francis turbine based on the assumption of a symmetric flow of the potential axis. The angle of the spiral is 360 ˚, which is more profitable for high-pressure turbines to reduce losses. Stay ring for better distribution of water. Designed spiral casing, stay ring and stay vanes are analyzed and tested using CFD for various guide vane openings and mass flow rates, both individually and with the entire turbine system. The assumption for the conservation of the angular momentum or potential flow is verified using CFD.
Using CFD for calculation of a spiral casing and stay vanes of a high-pressure Francis turbine
Keywords: статорне кільце; кут охоплення; розтруб; зуб; коефіцієнт корисної дії; гідравлічні турбіни; робоче колесо; stay ring; nose angle; bell mouth